Exploring the use of open data to support citizen-led initiatives for sustainable urban development in East Africa - Roza, Vasileva (2022)
In the last two decades, both the academic realm and urban governance practice have seen a rising interest in smart cities and open data to aid sustainable urban development and citizen engagement. However, little is currently known about data-driven citizen-centric practices ‘on the ground’. Research to date has been scarce and focused primarily on the experience in countries of the ‘Global North’. Therefore, the knowledge gap this work aimed to bridge was to develop an understanding of how open data are used to support citizen-led initiatives that address sustainable development in cities in the ‘Global South’.